Synthesis and structure of organometallic derivatives of 1,2,3,4,5,6,7,8-octamethyl-1,5-dihydro-s-indacene - Barlow, S; Cary, DR; Drewitt, M; OHare, D (1997)
A new fused-ring compound 1,2,3,4,5,6,7,8-octamethyl-1,5-dihydro-s-indacene (H 2L 1) has been synthesized from p-xylene. Three transition-metal derivatives [Mn(η 5-HL 1)(CO) 3], [Rh(η 5-HL 1)(η-C 5Me 5)] +[SbF 6] - and [Cr(η 6-H 2L 1)(CO) 3] have been characterised: spectroscopic and crystallographic data for these compounds show the ligand system is strongly electron donating. Although H 2L 1 is readily deprotonated to the monoanion by potassium metal or potassium hydride, surprisingly we have been unable to form (L 1) 2-. The crystal structure of [K] +[HL 1] -·19-crown-6 reveals the potassium ion to be sandwiched between the crown ether (1,4,7,10,13,16-hexaoxacyclooctadecane) and the (HL 1) - anion.